Exploring Songs as a Novel Tool for Enhancing Arabic and English Language Learning at State Islamic University - Erlangga, Rifqi Aulia; Bahroni, Bahroni (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study attempts to demonstrate the language acquisition theory, which says humans are natural learners who can learn by habituation. There is a song called Kun Fayakun, which has the same tune as Maroon 5's popular song Memories. This study examines the effectiveness of teaching Arabic simultaneously with English using that song for students. Sixty-four first-year UIN Salatiga students from Indonesia's various regions were requested to sing it in two versions, analyze the lyrics in two languages (Arabic and English), and map new vocabulary learned from the song. This study's data analysis will utilize a qualitative descriptive method based on experiment outcomes. Even though the respondents' initial English and Arabic abilities were rudimentary, with an average score of 6.5 out of 10, they stated that this multilingual popular song-based experiment provided them with a lot of information and new terminology in a pleasant and challenging way. These findings show that studying Arabic and English through popular song media can be a successful and entertaining technique for students.